The Quality of the Tribosystem as a Factor of Wear Resistance - Vojtov, Viktor; Biekirov, Abliatif; Voitov, Anton (International Journal of Engineering and Technology, 2018)
The purpose of this work was to develop a criterion for estimating the quality factor of the tribosystem and to assess its effect on wear rate, friction coefficient and run-in time. The basis of the methodological approach when developing a criterion for the quality of the tribosystem is the parameters that take into account the construction of the tribosystem, the thermal diffusivity of materials and the loading conditions of the tribosystems.The definition of the quality of the tribosystem has been further developed, which, unlike the known one, takes into account the geometric dimensions and kinematic scheme of the tribosystem, the thermal diffusivity of materials and the rate of propagation of deformation in the surface layers of the triboelement materials during their contact interaction. Theoretical and experimental studies established the relationship between the quality value, wear rate and the friction coefficient in the process of running-in. It is shown that the increase in quality helps to reduce the above-mentioned parameters.The relationship between the running-in time and the quality value is established. It is shown that the process of running-in can be controlled. To reduce the running-in time, it is necessary to reduce the sliding speed during the transient process and to increase the tribological properties of the lubricating medium. The presented theoretical and experimental studies allow us to state that the quality of tribosystems Q can be a measure of the potential ability of the tribosystem to adapt (adapt) to operating conditions, providing the maximum resource.
Keywords: frictional force; material compatibility; modelling; the quality of the tribosystem; the criterion for the quality factor of the tribosystem; tribosystem; wear rate.